Analisis Faktor yang Mempengaruhi Kesulitan Penggunaan Bahasa Baku pada Mahasiswa Papua Stambuk 2024 di Lingkungan Universitas Negeri Medan: Penelitian - Dina Rosanna Sipahutar; Lia Ima Triwani Siahaan; Muhammad Khadafi Chaniago; Rony Bayer Tamba; Sartana Pransiska Hutabarat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to identify the factors causing difficulties and the views of Papuan students regarding the use of standard Indonesian in an academic environment, as well as to design effective learning strategies to improve their abilities. Standard language is a variation of language used in formal contexts as a standard of communication, which not only functions as a tool for conveying ideas, but also serves as the main foundation for students' academic success. This study adopts a library research approach through the collection and analysis of data from books, journals, notes, and relevant reports, combined with quantitative methods using test instruments (quizzes through the Quizizz application) and questionnaires to measure respondents' understanding and views. The research population consisted of Papuan students enrolled in the 2024 academic year at Medan State University, with a sample of 27 respondents selected through purposive sampling. The results showed that these students experienced various difficulties in applying standard Indonesian, including oral communication, writing scientific reports, and formal interactions with lecturers and peers. The main inhibiting factors included the habit of using regional languages or Papuan dialects, low self-confidence, and minimal encouragement from the campus environment. However, the majority of respondents showed a positive attitude in the form of pride in using standard language, which could be used as capital for developing language skills. Therefore, systematic coaching strategies are needed from the campus, such as academic writing training, standard language discussion forums, lecturer assistance, and student organization support, in order to accelerate academic-social adaptation and strengthen the role of Indonesian as a unifying language in higher education.